Evaluating Realistic CPR Performance And Compression Quality In Field Resuscitation Teams (The Review of Diabetic Studies, 2025)
High-quality cardiopulmonary resuscitation (CPR) remains the most critical determinant of survival following cardiac arrest. While simulation-based training has improved the theoretical competence of healthcare providers, performance in real-world resuscitations often falls short of recommended standards. This review examines the realistic performance of CPR in field settings, focusing on the measurable indicators of quality—compression depth, rate, and continuity—and the psychological, physiological, and environmental factors influencing them. Evidence from 2016–2025 demonstrates a consistent performance gap between simulated and actual resuscitations, with stress, fatigue, and contextual challenges contributing to decreased compression accuracy and increased interruptions. The review also explores the role of team coordination, leadership, and feedback technology in mitigating these deficits. Emerging innovations such as real-time feedback systems, stress-adapted training, and continuous quality improvement (CQI) programs are discussed as potential solutions for bridging the simulation–reality divide. By integrating mechanical, human, and environmental dimensions into CPR evaluation and training, healthcare systems can promote realistic competence that translates into improved patient outcomes and sustained survival rates.